Analysis of Factors Causing Garbage Accumulation in The Tanjung Karang Coastal Area: Analisis Faktor Penyebab Penumpukan Sampah di Wilayah Pesisir Tanjung Karang - Ulya, Irtiqa; Pramana, Valhalla Yudha; Sahruramadhan, Syaum; Pratiwi, Nadia Tarissya (Yayasan Siti Widhatul Faeha, 2025)
Tanjung Karang Beach in Mataram City faces serious waste accumulation due to rising human activities, especially tourism. This study aims to identify the types and sources of waste and analyze the main contributing factors. A qualitative approach was used through field observations, interviews, and literature reviews. The results show that inorganic waste, particularly single-use plastics and styrofoam, dominates the area. The main sources include tourist activities, river runoff, and marine debris. Using a Fishbone Diagram, four contributing factors were identified: (1) Machine limited infrastructure and budget; (2) Method irregular waste collection and weak implementation of the 3R principle; (3) Man low awareness and careless littering; and (4) Material inadequate trash bins. The study concludes that waste accumulation in Tanjung Karang is a multidimensional issue involving technical, behavioral, and institutional aspects. This research contributes to understanding coastal waste problems and recommends improving infrastructure, promoting community education, enforcing regulations, and strengthening collaboration between stakeholders to ensure sustainable coastal tourism.